Upaya Mempertahankan Hasil Belajar Siswa Kelas VIII SMP Negeri 03 Tugu Trenggalek dengan Menggunakan Metode Information Search pada Materi Sikap Terpuji Khulafaur Rasyidin dalam Pembelajaran Daring Tahun Ajaran 2020/2021 - Konik'atin, Konik'atin (Jurnal Likhitaprajna, 2020)
During the Covid-19 pandemic, Islamic Religious Education experienced problems caused by the online learning system. The purpose of this study was to describe the learning outcomes of class students using the information search method on Khulafaur Rasyidin's Praise Attitude during learning. This type of research is classroom action research. This study used two cycles. Each cycle went through four stages which were adapted from the Kemmis & McTaggart model, namely (1) planning; (2) acting or acting; (3) observation or observing; (4) reflection or reflecting. The research subjects were students of class VII SMP Negeri 03 Tugu of Trenggalek as many as 47 people. The instrument used is a test. The Data Analysis Technique uses percentage and average value techniques from each cycle. The results showed that the percentage of learning completeness was 85%. 7 students did not complete it and 34 people had completed it. While in Cycle II, the classical completeness rate was 92.5%. Compared to the first cycle of 85%. the highest value in cycle II was achieved with a value of 95 and the lowest value of 75.